GUIDELINES FOR COMMUNITY-BASED TOURISM DEVELOPMENT AT BANG MAE-MAI BANG YAI BANG PLA-MA SUPHANBURI PROVINCE - Thong Khamkerd; Watcharaphan Sansit (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2019)
This paper aimed to 1) study Bang Mae Mai Community in terms of area, 2) evaluate the tourism potential held by Bang Mae Mai Community, and 3) propose the guidelines to develop Bang Mae Mai Community’s tourism. This study was a mixed method of quantitative and qualitative approaches. Participation Action Research was employed. The data collection was from the document, survey, in-depth interview, and focus group. The instruments were the interview form, checklist, and conversations. Then, the data were analysed. The findings were as follows: 1) In terms of Bang Mae Mai Community’s area, the tourism was held as a group led by Bang Mae Mai’s villagers. Tourists can participate with the tourism activities there such as Thai ways of life and Thai wisdom in Bang Mae Mai Community. 2) The research found that overview of tourism potential at Bang Mae Mai Community was excellent. Interm of details ranking from highest level to least; 1) the elevation of the quality of life; 2) the community – based tourism management; 3) the conservation of local culture; 4) the facilities and conveniences for the tourist and 5) tourism management by Bang Mae Mai community. 3) The seven guidelines gained under this study were proposed namely, tourism management development by Bang Mae Mai Community, tourism marketing development by Bang Mae Mai Community, tourists’ service development, data management and interpretation by Bang Mae Mai Community, tourism promotion by Bang Mae Mai Community, staff’s tourism ability development, and tourists’ safety.